2022
DOI: 10.1007/s40719-022-00223-7
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Suicide—Understanding Unique Risks and Opportunities for Trauma Centers to Recognize, Intervene, and Prevent a Leading Cause of Death

Abstract: Purpose of Review This provides up-to-date epidemiology of adolescent suicide and risk factors for suicide and highlights the overlap of risks for suicide and injury. It reviews signs and symptoms, and the up-to-date evidence on screening for depression, post-traumatic stress disorder (PTSD), suicide, substance abuse, and lethal means, and offers strategies of implementation in trauma centers. Recent Findings The incidence of adolescent suicide has continued to rise in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…30,31 Undetected and untreated disorders may also lead to self-harm via increased risks of suicidal ideation, which became the second leading cause of mortality among adolescents aged 10-19 in the United States based on prepandemic data from 2019. 32 Additionally, youths struggling with emotional problems may adopt unhealthy coping strategies, such as substance abuse. 33,34 In the long-term, adults who have experienced mental health problems during childhood or adolescence may be at risk of developing substance dependence, having reduced earning potentials, or having difficulty forming long-lasting social relationships.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Undetected and untreated disorders may also lead to self-harm via increased risks of suicidal ideation, which became the second leading cause of mortality among adolescents aged 10-19 in the United States based on prepandemic data from 2019. 32 Additionally, youths struggling with emotional problems may adopt unhealthy coping strategies, such as substance abuse. 33,34 In the long-term, adults who have experienced mental health problems during childhood or adolescence may be at risk of developing substance dependence, having reduced earning potentials, or having difficulty forming long-lasting social relationships.…”
Section: Introductionmentioning
confidence: 99%
“…This is, perhaps, not surprising that the statistics of suicide and homicide also increased in line with the numbers of depression, and have become the third-leading cause of death in 15-19-year-olds as reported by WHO. According to Hink et al, [2], this age group is 4 times more likely to die by committing suicide compared to other older adolescents.…”
Section: Introductionmentioning
confidence: 98%
“…As for the treatment, disturbed adolescents need to undergo a number of sessions in psychotherapy but the limitations in the current talk-based treatment may lead to negative experiences among the adolescents [3]. They also face difficulty expressing their feeling verbally and may also deny that they are suffering from depression [2]. Adolescents with depression also may have limited knowledge regarding depression, such as the differences between normal sadness and depression, early symptoms and impacts that could affect their daily life.…”
Section: Introductionmentioning
confidence: 99%
“…According to estimates from the World Health Organization (WHO), suicide was the fourth leading cause of death for youth between aged 15 to 29 globally in 2019 ( WHO, 2021 ). Data from the United States in 2019 indicated that suicide was the second leading cause of death for children aged 10 to 19 ( Centers for Disease Control and Prevention, n.d. ; Hink, Killings, Bhatt, Ridings, & Andrews, 2022 ). Children and adolescents are one of the most vulnerable groups to suicide during COVID-19 pandemic ( Efstathiou et al, 2022 ; Farooq, Tunmore, Wajid Ali, & Ayub, 2021 ), and thus the ongoing COVID-19 pandemic provides a unique opportunity to identify factors that might shape suicide ideation and behavior in children and adolescents, having implications for suicide prevention and intervention.…”
Section: Introductionmentioning
confidence: 99%